MicroRNA expression is associated with auditory dysfunction in workers exposed to ototoxic solvents and noise - Sisto, Renata; Moleti, Arturo; Capone, Pasquale; Sanjust, Filippo; Cerini, Luigi; Tranfo, Giovanna; Massini, Giulia; Buscema, Sara; Buscema, Paolo Massimo; Chiarella, Pieranna (Frontiers in Public Health, 2022)
This study is part of a project on early hearing dysfunction induced by combined exposure to Volatile Organic Compounds (VOCs) and noise in occupational settings. In a previous study, 56 microRNAs were found differentially expressed in exposed workers compared to controls. Here, we analyze the statistical association of microRNA expression with audiometric hearing level (HL) and Distortion Product Otoacoustic Emission (DPOAE) level in thate subset of differentially expressed microRNAs. The highest negative correlations were found, for HL, with miR-195-5p and miR-122-5p, and, for DPOAEs, with miR-92b-5p e miR-206. The homozygous (mut) and heterozygous (het) variants of the gene hOGG1 were found disadvantaged with respect to the wild-type (wt), as regards the risk of hearing impairment due to exposure to VOCs. An unsupervised Artificial Neural Network (Auto Contractive Map) was also used to detect and show, using graph analysis, the hidden connections between the explored variables. These findings may contribute to the formulation of mechanistic hypotheses about the hearing damage due to co-exposure to noise and ototoxic solvents.